Evaluation of calcium-carboxylate MOFs (Ca-MOFs) as promising adsorbents for simultaneous adsorption of endocrine disruptors compounds (EDCs) from aqueous solutions - Roslan, Muhammad Qusyairi Jori; Aris, Ahmad Zaharin; Sukatis, Fahren Fazzer; Zainuddin, Azim Haziq; Mohd Basyaruddin, Abdul Rahman; Lim, Hong Ngee; Mohd Isa, Noorain (Academic Press, 2025)
This study explores the development and evaluation of calcium-based carboxylate metal-organic frameworks (Ca-MOFs) for the adsorption and removal of endocrine-disrupting compounds (EDCs) from aquatic environments. Three Ca-MOFs; Ca-H2BDC, Ca-H3BTC, and Ca-H4BTC were synthesized and systematically assessed for their adsorption performance, mechanism, and regeneration capability. Among the tested frameworks, Ca-H2BDC exhibited the highest adsorption capacities, achieving maximum uptake values of 111 mg/g for bisphenol A (BPA), 164 mg/g for bisphenol F (BPF), and 135 mg/g for perfluorooctanoic acid (PFOA) under optimized conditions (0.005 mg/L initial concentration, 40 mg adsorbent, 25 °C, 40 min). These capacities exceeded those of Ca-H3BTC (BPA: 84 mg/g, BPF: 126 mg/g, PFOA: 85 mg/g) and Ca-H4BTC (BPA: 85 mg/g, BPF: 130 mg/g, PFOA: 86 mg/g), highlighting the superior performance of Ca-H2BDC, particularly toward plasticizers. The adsorption isotherms closely followed the Langmuir model, whereas the adsorption kinetics followed a pseudo-second-order model. Meanwhile, thermodynamic reveals endothermic and spontaneous (ΔH > 0 and ΔG < 0). Mechanistic studies supported by FTIR and SEM revealed that adsorption was primarily driven by hydrogen bonding, electrostatic attraction, and π-π interactions. Density functional theory (DFT) calculations further confirmed the strong stabilization of host-guest complexes, with a binding energy of −92 kJ/mol. Regeneration and reusability tests, along with water matrix evaluations, demonstrated that Ca-H2BDC offers promising potential for efficient micropollutant removal in realistic water treatment applications.